Implementation of Free Education Programs in Improving Access to Education in Surabaya City - Mahendra Raditya Chasasi Saputra; Muhammad Yasir Danhas Araya Putra (Income Journal Of Economics Development, 2026)
The free education program in the city of Surabaya, which was implemented through Regional Regulation No. 16 of 2012 and strengthened by its derivative policies, is designed to eliminate cost barriers in accessing primary and secondary education. However, the effectiveness of this program in improving equitable access to education—especially for vulnerable groups—has not been comprehensively researched and based on longitudinal data. This study aims to analyze the impact of the implementation of free education programs on improving access to education in Surabaya during the 2015–2023 period, focusing on the Gross Participation Rate (APK), School Dropout Rate (APS), and the spatial distribution of education access between regions. The method used is quantitative-descriptive research with a case study approach, using secondary data from the Surabaya City Education Office, the Central Statistics Agency (BPS) of East Java, and program evaluation documents. The analysis is carried out through trend analysis and cross-period comparison. The results showed that the APK SD/MI increased from 93.2% (2015) to 98.7% (2023), the APK for SMP/MTs from 87.6% to 96.3%, while the APS decreased significantly from 2.8% to 0.6%. However, there is a persistent spatial disparity between the city center and suburban areas, especially in West and East Surabaya. This research contributes to the education policy literature by identifying the determinants of program implementation success and gaps that need to be addressed through a targeted intervention approach.